A Navigation and Control System for a Robot in Indoor/Outdoor Environments - Al Khatib, Ehab (2016)
A Master of Science thesis in Mechatronics Engineering by Ehab Al Khatib entitled, "A Navigation and Control System for a Robot in Indoor/Outdoor Environments," submitted in May 2016. Thesis advisor is Dr. Mohammad A. Jaradat and thesis co-advisor is Dr. Mamoun Abdel-Hafez. Soft and hard copy available.